PERAN BAITUL MAAL HIDAYATULLAH DALAM MENYALURKAN INFAK KE PONDOK PESANTREN NURUL IMAN HIDAYATULLAH - Syahidah, Aulia Nisa Asy; Santi, Mei (LPPM STAI Muhammadiyah Probolinggo, 2024)
Baitul Maal Hidayatullah is a social organization that collects zakat, infaq, sadaqah, waqf and grants in the form of corporate and social responsibility funds and then distributes them through educational, da'wah, social and economic programs throughout the country. One of the programs that aims to build mental and cognitive strength for the next generation using an educational approach is scholarships for students who are financially disadvantaged. With this program, Baitul Maal Hidayatullah captures orphans and poor children through the Nurul Iman Hidayatullah Islamic boarding school which is located in Ketanon Village, Kedungwaru District, Tulungagung Regency. So that orphaned and poor students are prosperous and their education is helped through the boarding school. This research examines how Baitul Maal Hidayatullah helps Nurul Iman Hidayatullah Islamic boarding school. The purpose of this research is to see how Baitul Maal Hidayatullah helps the Nurul Iman Hidayatullah Islamic boarding school. This research applies a type of qualitative research using descriptive methods. The data collection method is by asking a few questions, seeing directly in the field and taking some documents or appropriate data. Data analysis techniques include adjustment, presentation and conclusion. The results of this study prove that Baitul Maal Hidayatullah is an organization that aims to collect zakat, infaq, sadaqah and waqf funds, which then one of the sources of funds in the form of infaq is distributed to mustahik. The infaq funds collected by Baitul Maal Hidayatullah are well channeled to the Nurul Iman Hidayatullah Islamic boarding school. Several programs to support the distribution of infaq include tahfidz santri scholarships, santri rice, santri construction, santri operations and cottage teacher operations. Keywords: Role, Baitul Maal, Hidayatullah, Infaq, Islamic Boarding School.